EFL STUDENTS’ PERCEPTIONS OF GOOGLE CLASSROOM IN JUNIOR HIGH SCHOOL ENGLISH LEARNING - Huwaida Syauqi Labibah; Sephia Difa Adila; Septian Maulana; Tri Wintolo Apoko (Universitas Wiralodra, 2024)
This study is aimed at investigating EFL students’ perceptions on the use of Google Classroom for English language learning in a junior high school. The study used a mixed method design, combining quantitative and qualitative data. The context of the study was EFL students from one of state junior high schools in Jakarta, Indonesia. Through a survey of 146 students and some selected students for interviews, the study examines various aspects of their experiences with the platform, including motivation, effectiveness, communication, and access to learning materials. The findings reveal a positive attitude among EFL students towards Google Classroom, with their acknowledging its benefits in enhancing motivation, facilitating interaction, and providing convenient access to resources. The study highlights the potential of digital tools like Google Classroom to address challenges in language education. Thus, this study suggests implications for English teachers seeking to optimize technology-enhanced learning environments, mainly in English learning in junior high schools.